Composition of Bacterial and Archaeal Communities in an Alkali-Surfactant-Polyacrylamide-Flooded Oil Reservoir and the Responses of Microcosms to Nutrients - Gao, Peike; Li, Yu; Tan, Lijie; Guo, Fenfen; Ma, Ting (Frontiers in Microbiology, 2019)
The microbial communities in alkali-surfactant-polyacrylamide-flooded (ASP-flooded) oil reservoirs have rarely been investigated compared to those in water-flooded oil reservoirs. Here, the bacterial and archaeal communities in an ASP-flooded reservoir and the adjacent water-flooded block, and responses of the microbial communities in microcosms to nutrients were investigated by 16S rRNA gene sequencing and cultivation. Compared with the water-flooded block, both the bacterial and archaeal communities inhabiting the ASP-flooded block had lower Sobs indices (91:232 and 34:55, respectively), lower Shannon indices (1.296:2.256 and 0.845:1.627, respectively) and higher Simpson indices (0.391:0.248 and 0.678:0.315, respectively). Halomonas (58.4-82.1%) and Anoxynatronum (14.5-18.2%) predominated in the ASP-flooded production wells, and were less than 0.05% in the bacterial communities of the adjacent water-flooded production wells, which were dominated by Pseudomonas and Thauera. Methanobacterium accounted for 65.0-94.5% of the archaeal communities inhabiting the ASP-flooded production wells, and Methanosaeta (36.7-94.5%) dominated the adjacent water-flooded production wells. After nutrients stimulation, the quantity of cultivable microorganisms increased from 103 /mL to 107 /mL. Community analysis indicated that the relative abundances of some species that belonged to Halomonas and Pseudomonas obviously increased, yet there were no oil emulsification or dispersion and changes of surface tension of the water-oil mixture. In addition, 6 alkali-tolerating strains showing 98% similarity of 16S rRNA genes with those of Halomonas alkalicola and Halomonas desiderata and 2 strains with 99% similarity with Pseudomonas stutzeri gene were isolated from the nutrients stimulated brines. In summary, this study indicated that Halomonas, Anoxynatronum, and Methanobacterium were dominant populations in the ASP-flooded reservoir, the extreme environment decreased microbial diversity, and restricted microbial growth and metabolisms.